The Accessibility of Tahfidz Al-Qur'an for Teachers with Disabilities at the Tahfidz Daarul Qur'an Islamic Boarding School - Jamil, Ahmad; Khaled, Naswan Abdo; Rasyid, Harun al (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThe purpose of this study was to investigate the implementation of tahfidz Al-Qur'an learning by disabled teachers at the Tahfidz Daarul Qur'an Islamic Boarding School Tangerang and the efforts of teachers with disabilities to create a welcoming environment during the implementation of tahfidz Al-Qur'an learning at the Tahfidz Daarul Qur'an Islamic Boarding School Tangerang.  This is a field study with a qualitative descriptive method. This study was carried out at Tangerang's Tahfidz Daarul Qur'an Islamic Boarding School. Tahfidz Al-Qur'an Teachers (blind and physically disabled) and the Tahifdz Bureau Head were among the informants. The data was gathered through observation, interviews, and literature study on the concept of disability in Islam. The findings of this study show that teachers with disabilities at the Tahfidz Daarul Qur'an Islamic Boarding School Tangerang are capable of effective educational communication, allowing them to carry out tahfidzul Qur'an learningn along with other tahfidz teachers. There is a change while completing the rote progress report in the mutaba'ah book. Additionally, teachers with impairments make an attempt to enforce the relevant regulations by Rewarding students who comply the regulation punishing students who are against the regulation.AbstrakTujuan dari penelitian ini adalah untuk menyelidiki pelaksanaan pembelajaran tahfidz Al-Qur'an oleh guru-guru penyandang disabilitas di Pondok Pesantren Tahfidz Daarul Qur'an Tangerang dan  upaya guru-guru penyandang disabilitas untuk menciptakan lingkungan yang ramah selama pelaksanaan pembelajaran tahfidzh Al-Qur'an di Pondok Pesantren Tahfidz Daarul Qur'an Tangerang. Ini adalah studi lapangan dengan metode deskriptif kualitatif. Penelitian ini dilakukan di Pondok Pesantren Tahfidz Daarul Qur'an Tangerang. Guru-guru Tahfidz Al-Qur'an (tuna netra dan penyandang disabilitas fisik) dan Kepala Biro Tahfidz adalah beberapa informan. Data dikumpulkan melalui observasi, wawancara, dan studi literatur tentang konsep disabilitas dalam Islam. Temuan dari penelitian ini menunjukkan bahwa guru-guru penyandang disabilitas di Pondok Pesantren Tahfidz Daarul Qur'an Tangerang mampu melakukan komunikasi pendidikan yang efektif, memungkinkan mereka untuk melaksanakan pembelajaran tahfidzul Qur'an bersama guru-guru tahfidz lainnya. Ada perubahan saat menyelesaikan laporan kemajuan hafalan dalam buku mutaba'ah. Selain itu, guru-guru dengan keterbatasan berusaha untuk menegakkan peraturan yang relevan dengan memberikan penghargaan kepada siswa yang mematuhi peraturan dan menghukum siswa yang melanggar peraturan.How to Cite : Jamil, A., Khaled, N. A., Al  Rasyid, H. (2022). The Accessibility of Tahfidz Al-Qur'an for Teachers with Disabilities at the Tahfidz Daarul Qur'an Islamic Boarding School. TARBIYA: Journal of Education in Muslim Society, 9(2), 123-134. doi:10.15408/tjems.v9i2.31326.